2008
DOI: 10.1203/pdr.0b013e318183f132
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fabry Disease in 352 Pediatric Patients in the Fabry Registry

Abstract: ABSTRACT:Fabry disease is an X-linked lysosomal disease caused by deficiency of ␣-galactosidase A. Signs and symptoms of Fabry disease occurring during childhood and adolescence were characterized in 352 Fabry Registry patients. At enrollment (median age 12 year), 77% of males and 51% of females reported symptoms. The median age of symptom onset was 6 year in males and 9 year in females. The most frequent symptom, neuropathic pain, was reported by 59% of males (median age 7 year) and 41% of females (median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
243
1
34

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(283 citation statements)
references
References 21 publications
5
243
1
34
Order By: Relevance
“…In vitro studies suggest that these elevations trigger a cascade of pathological processes, including inflammatory and fibrotic responses that cause progressive damage to multiple organs (Germain 2010). In males with classic FD, early signs and symptoms, including neuropathic pain, hypohidrosis, and gastrointestinal dysmotility, usually appear in early childhood (Hopkin et al 2008), and life-threatening renal, cardiac, and cerebrovascular complications typically develop by the fourth or fifth decade of life (Germain 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies suggest that these elevations trigger a cascade of pathological processes, including inflammatory and fibrotic responses that cause progressive damage to multiple organs (Germain 2010). In males with classic FD, early signs and symptoms, including neuropathic pain, hypohidrosis, and gastrointestinal dysmotility, usually appear in early childhood (Hopkin et al 2008), and life-threatening renal, cardiac, and cerebrovascular complications typically develop by the fourth or fifth decade of life (Germain 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal dose of agalsidase has long been a matter of debate (Desnick 2004), and identification of the biochemically and clinically most effective dose has been hampered by the slowly progressive nature of FD that lacks reliable, predictive biochemical or clinical surrogate end points. Additionally, the clinical presentation of FD is highly heterogeneous and the timing of symptom onset highly variable (Eng et al 2007;Hopkin et al 2008). There have been no randomized, double-blind trials of patients matched for sex, age, and disease severity to allow a direct comparison of the effectiveness of agalsidase beta and agalsidase alfa at their approved doses (Desnick and Schuchman 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The initial signs and symptoms of FD frequently include neuropathic pain in the extremities, hypohidrosis, angiokeratomas, and gastrointestinal discomfort. 3 Over a period of decades, the accumulation of glycosphingolipids impairs vital organ function, putting patients at risk of developing renal failure, stroke, and cardiovascular dysfunction. [4][5][6] Because it is an X-linked disorder, hemizygous males typically experience the most severe manifestations of FD, 1 but heterozygous females can also develop serious complications.…”
mentioning
confidence: 99%
“…Our data, i.e., 90% of males and 47% of females reporting distal extremity pain, are in line with previously reported observations. Analyses of data from two Fabry's registries have shown that large proportions of children and adolescents (boys: 60 -80%, girls: 40 -60%) report neuropathic pain; boys often a few years earlier than girls (24,25). In many individuals, the pain had not been recognized as an early symptom of FD and correct diagnosis was delayed until well into adulthood.…”
Section: Discussionmentioning
confidence: 99%